2020
DOI: 10.1186/s12891-020-03424-w
|View full text |Cite
|
Sign up to set email alerts
|

Return to play after hip arthroscopy among tennis players: outcomes with minimum five-year follow-up

Abstract: Background: Playing tennis is associated with various movements that can lead to labral injuries and may require arthroscopic surgery. While hip arthroscopies have demonstrated good outcomes in athletes, there is limited literature reporting patient reported outcomes (PROs) and return to sport (RTS) in competitive or recreational tennis players after arthroscopic hip surgery. Therefore, the purpose of the present study was to (1) report minimum fiveyear PROs and RTS in tennis players who underwent arthroscopic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…Patients with symptomatic FAI have been shown to require more flexion at the hip to achieve the sitting position owing to their inability to compensate through the lumbar spine. 26,46,48,54,56 Furthermore, patients with symptomatic FAI have been shown to have less spine flexion as compared with a non-FAI control group and even patients with asymptomatic FAI. The effect of lumbopelvic motion has been well described in previous literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with symptomatic FAI have been shown to require more flexion at the hip to achieve the sitting position owing to their inability to compensate through the lumbar spine. 26,46,48,54,56 Furthermore, patients with symptomatic FAI have been shown to have less spine flexion as compared with a non-FAI control group and even patients with asymptomatic FAI. The effect of lumbopelvic motion has been well described in previous literature.…”
Section: Discussionmentioning
confidence: 99%
“…RTS was defined as a patient’s return to competitive participation in his or her sport at the same level as or higher than that of before surgery within 2 years postoperatively. 16,46…”
Section: Methodsmentioning
confidence: 99%
“…It is worth noting that the high rate of injury occurrences in tennis does not only affect the career of athletes but also has significant economic impacts on both athletes and concerned authorities ( 32 ). Despite these problems, comprehensive programs for tennis injury prevention are either lacking or inadequate ( 33 ). As such, research has indicated the need for systematic investigation to recommend useful strategies for the prevention and management of tennis-related injuries ( 4 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…1,29 Although previous studies have addressed PROs and RTS rates after HA, most of the available literature discussing outcomes among athletes and nonathletes are limited to short-term follow-up. 17,18,20 Moreover, many of the current 5-year outcome studies on athletes lack direct comparisons between competitive athletes (CAs) and Controls (ie, case series), 6,7,22,25,28,30,34,43 or include a broad definition of a CA (ie, recreational athletes, high school, organized amateur), making it challenging to discern conclusions on how outcomes of high-level CAs compare with those of Control patients. 6,7,[22][23][24][25]28,30,34,43 As HA continues to become a more prevalent choice of treatment for FAIS, additional studies investigating long-term durability and efficacy are needed.…”
mentioning
confidence: 99%
“…17,18,20 Moreover, many of the current 5-year outcome studies on athletes lack direct comparisons between competitive athletes (CAs) and Controls (ie, case series), 6,7,22,25,28,30,34,43 or include a broad definition of a CA (ie, recreational athletes, high school, organized amateur), making it challenging to discern conclusions on how outcomes of high-level CAs compare with those of Control patients. 6,7,[22][23][24][25]28,30,34,43 As HA continues to become a more prevalent choice of treatment for FAIS, additional studies investigating long-term durability and efficacy are needed. 29,35,37 Therefore, the primary purpose of this study was to (1) determine differences in midterm clinical outcomes at minimum 5-year follow-up between patients who are high-level CA versus propensity-matched Controls undergoing HA for FAIS, and (2) determine whether achievement rates of minimal clinically important differences (MCID) and patient acceptable symptom states (PASS) differ between the 2 groups.…”
mentioning
confidence: 99%